6(x-7)-12=20x-222

Simple and best practice solution for 6(x-7)-12=20x-222 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-7)-12=20x-222 equation:


Simplifying
6(x + -7) + -12 = 20x + -222

Reorder the terms:
6(-7 + x) + -12 = 20x + -222
(-7 * 6 + x * 6) + -12 = 20x + -222
(-42 + 6x) + -12 = 20x + -222

Reorder the terms:
-42 + -12 + 6x = 20x + -222

Combine like terms: -42 + -12 = -54
-54 + 6x = 20x + -222

Reorder the terms:
-54 + 6x = -222 + 20x

Solving
-54 + 6x = -222 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
-54 + 6x + -20x = -222 + 20x + -20x

Combine like terms: 6x + -20x = -14x
-54 + -14x = -222 + 20x + -20x

Combine like terms: 20x + -20x = 0
-54 + -14x = -222 + 0
-54 + -14x = -222

Add '54' to each side of the equation.
-54 + 54 + -14x = -222 + 54

Combine like terms: -54 + 54 = 0
0 + -14x = -222 + 54
-14x = -222 + 54

Combine like terms: -222 + 54 = -168
-14x = -168

Divide each side by '-14'.
x = 12

Simplifying
x = 12

See similar equations:

| 3.3d-7.2=0.8d+7.3 | | (12)-24=x | | 6(x-4)=6(x-1) | | 15=4(3.14)r | | 12*-24= | | 5n-5=-6n-16 | | a/15+4/15=9/5 | | 5(x-4)+4x=9x-20 | | 6x-2.6666666=6x | | -6(x+8)+365=11+18 | | a(x+c)=2ad+c | | 4x^2-6x+3= | | -3(x+9)+97=32+11 | | y=280-4x | | 3(5x+3)+58=8x+4 | | y=0.5x-8 | | -44+12x=12+10x | | 6(x-5)=36 | | -9=4n-n | | 2-5w=-38 | | 3h+c=300 | | 5w-70=9w | | 6-7r=-50 | | 3a+8-5a=-7(a+1) | | -1(x+5)=3x+15 | | 4(x+1)5(x+2)= | | 9ln(6x)=63 | | 6x+3(x+7)=-7 | | 2y-17+y=180 | | -3.14y=53.38 | | 7.50h+100=550 | | 2+6h=10+3h |

Equations solver categories